Learning Law from Customary Village: Implementation of the Value of Consencus Deliberation in the Election of Customary Village in Bali - I Putu Sastra Wibawa; Ida Bagus Alit Yoga Maheswara; Komang Indra Apsaridewi (Universitas Negeri Semarang, 2024)
Customary Villages have autonomy in carrying out their duties and authorities as well as the right to regulate and take care of their own households, of course, they must have a Customary Village government in accordance with the traditions that have been hereditary in Customary Villages in accordance with their respective customary laws. The process of electing Customary Village Leaders in Bali which prioritizes the principles of consensus deliberation which is part of the implementation of the autonomy of Customary Village Communities in Bali in electing Customary Village Leaders in customary life is in line with the Indonesian Nation and Nation State's life handle, namely Pancasila. This paper uses a normative legal research method. The problem is discussed with a legal and regulatory approach, a legal analysis approach and a legal concept approach. The determination of Customary Village Leaders in Bali in the framework of legal pluralism and its implementation in Customary Villages in Bali, currently is not only guided by regional law regulations in the form of Regional Regulations on Customary Villages in Bali, buts must also be guided by customary laws that apply in each Customary Village in Bali in the election of Customary Village Leaders in Bali.